(untitled) (Raparin Journal of Humanities (RJH), 2020)
Lexical authorship is one of the most important efforts that cannot be underestimated because of its role in understanding the meanings and semantics of words. Studies have proven that Arabic is one of the most widely used languages ​​in the world. Arabic or Dad has received more attention than other languages, so the crown of the bride is one of the largest dictionaries that contain a huge number of vocabulary including words related to diseases. For leather. Dermatology or dermatology is a medical specialty that deals with diseases of the skin and mucous membranes. It is also concerned with nail and hair diseases and is traditionally associated with sexually transmitted diseases. The doctor in this medical branch is often called a dermatologist. Of external influences and visible. Skin diseases and disorders differ in the severity of their symptoms, their causes, and the strength of their effect; some cases may be mild, transient and may be life-threatening, so the research aims to study and show the words skin diseases mentioned in the bride’s crown Zubaidi distributed on diseases related to pimples, skin color change, And dissected superficial and flesh contact, tumors in addition to hair diseases, which are classified as skin diseases, and concluded the study with the conclusion of the most important findings of the research, including: The most diseases that affect the skin phenomenon, which makes it a social disease more than organically, most of the words mentioned Zubaidi, a skin still Mskhaddmhaly this day and widespread medical, unlike synonymous words that have disappeared and have become unused.